Toxicity of food supplements as an adjuvant for COVID-19 treatment or prevention - Zoran Zhivikj; Tanja Ivanovska; Lidija Tozi; Tatjana Panovska (Journal of Tropical Life Science, 2022)
Commercially available food supplements, especially vitamins and minerals are becoming increasingly popular in the era of COVID-19 disease. Sales of food supplements increased dynamically because of the belief that they could be more effective than conventional antiviral or corticosteroid drugs as well as missing of the specific medical therapy for preventing or treating this disease. The greatest interest is associated to immune-related nutrients and antioxidant agents, among which vitamin C, vitamin D, vitamin E, selenium and zinc. All of these are currently under clinical investigation for possible application in prevention and treatment of COVID-19. The main concern is that apart the use in the cases with deficiency of vitamin D or C, selenium and zinc, there are no convincing evidence to support the role of nutritional supplementation in COVID-19 prevention. Further, large intakes may worsen the diet and many people gained weight as additional risk factor of developing complications during the course of the disease, and finally inappropriate doses may initiate toxicity. Hence, additional studies assessing the impact as well as the mechanism of action of the specific nutrients on the incidence and progress of COVID-19 in relation to age, nutritional status, wellbeing and particular to existing co-morbidities, are entailed. Moreover, whether and which specific nutrients has a positive effect against COVID-19 in healthy and well-nourished individuals, should be also evaluated. Awaiting the scientific evidence, we have reviewed mechanisms, efficacy and safety of immune-boosting and/or antioxidant nutrients proposed to be used as food supplements in prevention and treatment of COVID-19.Ã‚Â